The Effect of Child Psychological Abuse on College Students’ Attitudes Toward Cyberbullying: The Mediating Role of Belief in a Fair World and Gratitude Traits - Chen, Shuxia (Transactions on Social Science, Education and Humanities Research, 2023)
To explore the effects of child psychological maltreatment on college students’ attitudes toward cyberbullying: the mediating roles of Just World Beliefs and Gratitude Trait. The Childhood Psychological Abuse Questionnaire, the Just World Beliefs Questionnaire, the Gratitude Scale, and the College Student Cyberbullying Attitudes Scale were used to investigate 1300 college students. Results: Fair World Beliefs and Trait Gratitude were found to be one of the mediating mechanisms through which childhood psychological maltreatment affected college students’ attitudes toward cyberbullying.